2020
DOI: 10.31234/osf.io/kvnwp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Connecting Self-Reported Social Distancing to Real-World Behavior During the COVID-19 Pandemic

Abstract: Social distancing is currently the single most effective method to reduce the spread of COVID-19. As such, researchers across varying fields are rushing to identify variables that predict social distancing and which interventions can heighten social distancing. Yet, much of this research relies on self-report measures (in part because of social distancing guidelines themselves). In two studies we examine whether self-reported social distancing overlaps with real-world behavior. In Study 1, individuals’ self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 31 publications
3
73
0
Order By: Relevance
“…Inferences should be made with care and consideration of our sampling method. Relatedly, and though recent COVID-19 research shows that self-reported measures of social distancing track actual behavior both at the individual and at the U.S. state level (Gollwitzer et al 2020), our results may be susceptible to common method bias (Favero and Bullock 2015). More details on our methodology-including similar results obtained from analyses without survey weights-are contained in the appendix, which also reports summary statistics (Table A1).…”
Section: Who Indicates the Most Willingness To Social Distance?mentioning
confidence: 87%
“…Inferences should be made with care and consideration of our sampling method. Relatedly, and though recent COVID-19 research shows that self-reported measures of social distancing track actual behavior both at the individual and at the U.S. state level (Gollwitzer et al 2020), our results may be susceptible to common method bias (Favero and Bullock 2015). More details on our methodology-including similar results obtained from analyses without survey weights-are contained in the appendix, which also reports summary statistics (Table A1).…”
Section: Who Indicates the Most Willingness To Social Distance?mentioning
confidence: 87%
“…Similarly, we focused on self-report of behavior, not actual behavior and there might be a gap between reported and actual health-protective behavior. However, recent research focusing on GPS movement data in the US during the COVID-19 outbreak suggests that self-report data might be used as a proxy for actual behavior ( Gollwitzer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, gatherings of people have still been observed in different countries even though full home confinement has been ordered (Valiante, 2020). In some countries, people have even gathered to protest the COVID-19 pandemic containment measures (Deutsche Welle, 2020), although social distancing has been regarded as the currently most effective way to slow the spread of COVID-19 (Gollwitzer et al, 2020). So, the question arises why do some people not stay at home even though these measures are imposed to slow the spreading of the COVID-19 pandemic?…”
Section: Human Behavior During a Pandemicmentioning
confidence: 99%